Antibacterial activity of Andrographis paniculata leaf extracts - Tipakorn N. (2014)
A study was conducted at the laboratory of Diagnosis and Research Centre, Department of Livestock Development, Wang Tong District, Phitsanulok Province, Thailand and the study was carried out to determine the antibacterial activity of Andrographis paniculata (Burm. f.) Nees extract with different solvents. AP leaves powder (andrographolide 7.30%) that was already tested for quality was used in this experiment. It was extracted in a series of three different solvents: distilled water, 70% alcohol and 85% alcohol. The antibacterial activity of each AP leaves solvent was analyzed by using agar disk diffusion method as antibacterial susceptibility test was placed in flasks and added solvent either distilled water, 70% alcohol or 85% alcohol (1:10 w/v). The flasks were placed in a shaking water bath at 50°C for 48 hr after which the solvents were filtered through filter paper (residue was not used). The extract solutions were put in a rotary evaporator and evaporated at 50°C until dry residues were left. These residues were weighed. Disk papers with a 5.8 mm diameter, were sterilized and dried. Then, the dry extract prepared was dissolved again with the same solvent and diluted with distilled water in proportions of 1:10, 1:100, 1:1000 (w/v) to determine which of these concentrations had a inhibitory effect on bacterial growth. 0.03 ml AP extract were added to each paper. After that it was placed in an oven and dried at 50°C overnight. 4 samples of bacteria from the Laboratory of Diagnosis and Research Centre, Department of Livestock Development were used in the experiment 1.1: S. typhimulium, S. spp., E. coli ATCC 25922 (standard), E. coli (from chicken). The bacteria were grown in Petri dishes with Mueller-Hinton Agar (MHA). The inoculum suspensions were compared with McFarland standard No. 0.5. After that the bacteria were spread over the surface of the MHA disks using sterilized swab. The experiment 1.2 was conducted after Experiment 1.1 was evaluated. It used the same method as Experiment 1.1 but the number of samples was changed to 14 samples with 3 types of bacteria: Salmonellae (sample 1 - 3), E. coli (sample 4 - 10) and P. multocida (sample 11 - 14) and only the concentration 1:10 w/v of the different AP extracts was used. As control Streptomycin 2 mg/ml was used. The Study in experiment 1.1 showed none of the used concentrations 1:10, 1:100 and 1:1000 of AP aqueous extract showed any antibacterial effect on S. typhimrium, S. spp., E. coli ATCC and E. coli (from chicken). Only the concentration 1:10 of 70% and 85% of alcoholic extract of AP showed moderate to intermediate activity to S. typhimurium with inhibition zones of 12 and 10 mm respectively. The minimum inhibitory concentration (MIC) of 70% and 85% alcoholic extract of AP were 1:10 according to this test. The lower concentrations of 1:100 and 1:1000 did not influence the bacteria growth. Results of experiment 1.2 showed the aqueous extract of AP 1:10 showed no antibacterial activity towards any of the bacteria tested. Also 70% and 85% alcoholic extract of AP 1:10 showed no antibacterial activity towards any of the Salmonellae and E. coli strains of bacteria tested. However, these two extracts of AP showed antibacterial activity towards three of the four tested P. multocida strains. Six of the seven tested E. coli strains, one of the two tested S. spp. and one of the four tested P. multocida showed resistance to the Streptomycin. Thus, AP leaves can be used as antibacterial agents against diarrhea is promising.